Criminal Law of Ukraine (Punishment and Other Criminal Measures: National Approach) : Training Manual - Стрельцов, Євген Львович; Streltsov, Yevhen L.; Стрельцов, Є. Л.; Туляков, Вячеслав Олексійович; Tulyakov, Viacheslav O.; Туляков, В. О.; Кузьмін, Едуард Едуардович; Kuzmin, Eduard E.; Кузьмін, Е. Е. (Odesa : Helvetica, 2020)
Criminal Law of Ukraine on punishment and other criminal measures is analysed in this training manual as a Part of scientific and educational project on formatting the academic background and training bachelors of law in English. The set of training sessions and basic ideas on Fundamentals of Punishment and other coercive measures in Ukraine in comparison with ECHR practice and modem Criminal Law concepts is given. The training manual was prepared under auspices of Fundamental scientific research "Euro integrational criminal-legal policy of Ukraine” No 0118U003677 and would be helpful for scholars in the field of comparative Criminal Justice, Future judges, detectives, investigators, prosecutors and members of the Bar.

Кримінальне право України щодо покарань та інших заходів кримінально-правового впливу аналізується у цьому навчальному посібнику як частина науково-освітнього проекту з форматування академічного досвіду та підготовки бакалаврів юридичних наук англійською мовою. Наведено комплекс навчальних занять та основні ідеї з Основ покарання та інших заходів примусового характеру в Україні у порівнянні із практикою ЄСПЛ та сучасними концепціями кримінального права. Навчальний посібник підготовлений під егідою Фундаментального наукового дослідження «Євроінтеграційна кримінально-правова політика України», державний реєстраційний номер 0118U003677, і буде корисним для науковців у галузі порівняльного кримінального права, майбутніх суддів, детективів, слідчих, прокурорів та членів адвокатури.
Streltsov Y. L. Criminal Law of Ukraine (Punishment and Other Criminal Measures: National Approach) : Training Manual / Ye. L. Streltsov, V. O. Tulyakov, E. E. Kuzmin ; Nat. Univer. "Odesa Law Acad.". — Odesa : Helvetica, 2020. — 80 p.
Keywords: кримінальне право України; criminal law of Ukraine; punishment and other criminal measures; покарання; підготовка бакалаврів юридичних наук англійською мовою; training of bachelors of law in English; Research Subject Categories::LAW/JURISPRUDENCE